The Spill Phenomenon in the Context of the Hadith Prohibition of Spelling Other People's Disgrace - Zur'aini Latifah Zahra; Uswatun Hasanah; Hedhri Nadhiran (al-Afkar, Journal For Islamic Studies, 2025)
Technological advances have led to an increase in phenomena that often occur, one of which is discussing other people's disgrace in various ways which is commonly referred to as the spill phenomenon. TikTok social media is a form of technological progress that is widely used by humans, thus providing a great opportunity to cause activities that have a negative impact and commotion. In this article, hadith will be the main discussion because it differs from previous research and hadith itself is an explanation or reflection of the Al-Qur'an. The hadith that will be used is the hadith narrated by Imam At-Tirmidhi because it is part of the Politikussitah, namely the Mu'tabar hadith books which are a reference for Muslims. This research uses a literature research design (library research). The data analysis technique used in this research is qualitative data analysis technique. The primary data source used in this research is the hadith narrated by Imam At-Tirmidhi number 2032 in the book Jami' At-Tirmidhi and secondary data sources in the form of articles, books and journals that are directly related to the research theme. The results of the discussion concluded that showing disgrace or spilling is an act that is prohibited by religion. However, scholars agree that this spill activity can be carried out under four conditions, namely to expose injustice, seek protection from injustice, ask for advice, and give a warning. In this condition, such as spill behavior, you still have to use manners or ethics, namely not openly exposing someone's disgrace and talking about other people to be introduced. If this spill is carried out outside of these four conditions and without applicable etiquette, the spill will lead to things that are prohibited in religion and lead to a negative realm which will make the act haram.